LIFT vs Fistulectomy: A Retrospective Cohort Study - Tabeer Malik, Nighat Nadeem, M. Nadeem Aslam (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Fistula-in-ano is defined as an epithelized abnormal tract connecting two surfaces; usually the rectal mucosa and perianal skin. The primary treatment for fistula is surgery for which many options are available. However, in this article, we will be discussing the comparison between LIFT and fistulectomy. Aim: To compare a conventional invasive technique of fistulectomy with a newly introduced minimally invasive LIFT procedure in terms of operative time, hospital stay, postoperative complications, and follow-up. Methods: A retrospective view of 135 patients was done who were operated on either by LIFT (n=59) (Group L) or fistulectomy (n=76) (Group F) over the period of three years and a comparison between two techniques was performed using Student’s t-test or Mann-Whitney test for continuous variables and Fisher’s exact test for categorical variables. Results: Our operative time for LIFT was greater than the fistulectomy. Post-operative pain was analyzed using the VAS pain scale, where Group L experienced less post-operative pain. Group F patients’ wounds took longer to heal as compared to Group L patients. Hence group L (LIFT) returned to work earlier. Post-operative complications such as wound discharge were reported more in Group F than in Group L. Same was observed in the case of post-operative infection rate. Two cases of wound granulation were observed in the case of LIFT (Group L) at one-month follow-up and one case of incontinence to flatus in the Group F group was documented at three-month follow-up in the patient’s record. Thirty-seven patients’ complained of itching in Group F compared to 10 in Group L. Patients who had seton, complained of setons related problems. Conclusion: LIFT was a promising and sphincter-saving technique that was simple and easy to learn with faster healing rates and better patient contentment. Keywords: LIFT, fistulectomy, fistula-in-ano